Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran Problem Based Learning (PBL) dengan Alat Bantu Papan Penjumlahan pada Mata Pelajaran Matematika di Kelas 4 SD Negeri 44 Cakranegara - Lailatul Baqiah; Hj. Nurhasanah; Efendi Harahap (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to improve the mathematics learning outcomes of fourth-grade students at SDN 44 Cakranegara on the topic of addition with regrouping through the implementation of the Problem-Based Learning (PBL) model supported by an addition board as instructional media. The background of this study was the low student learning outcomes caused by difficulties in understanding addition concepts and the limited use of interactive learning methods and concrete media. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 28 students. Data were collected through observation and learning outcome tests. The results showed a significant improvement in students’ ability to solve addition operations after the implementation of the PBL model assisted by the addition board. In the initial test, only 14.2% of students achieved mastery learning, with an average score of 59.6. These findings indicate that the use of the PBL model and concrete media such as the addition board can enhance students’ understanding of mathematical concepts and improve overall learning outcomes.